2022
DOI: 10.1111/ajgw.12564
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amino acids, and their interaction with volatiles and polyphenols, on the sensory properties of red wine

Abstract: Background and Aims: The effect of amino acids, and their interactions with volatiles and other non-volatiles, on inmouth sensory properties of red wines is not known. This knowledge gap has been studied in a series of comprehensive sensory experiments. Methods and Results: A solvent-assisted flavour evaporation extract of Shiraz wine volatiles, a de-aromatised polyphenolic extract and amino acids were added to model wine and wine systems. Using full factorial designs, samples were evaluated by sensory quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…Recently, Espinase Nandorfy et al [21] demonstrated the sensory infuence of the residual amino acid proline in dry red wine, which increased perceived sweetness, fruit favour, and viscous mouthfeel, while diminishing bitterness and astringency. Although the proline concentration is reported to be lower in white wines (0.025-1.4 g/L) compared to red wines (0.018-4.4 g/L) as reviewed by Gutiérrez-Gamboa et al [43], the range can span across the sensory detection threshold reported in water of approximately 2 g/L [44] and has been linked to wine "body" previously [45].…”
Section: Assessing the Association Of Pmt And 2fmt With Smoky/mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Espinase Nandorfy et al [21] demonstrated the sensory infuence of the residual amino acid proline in dry red wine, which increased perceived sweetness, fruit favour, and viscous mouthfeel, while diminishing bitterness and astringency. Although the proline concentration is reported to be lower in white wines (0.025-1.4 g/L) compared to red wines (0.018-4.4 g/L) as reviewed by Gutiérrez-Gamboa et al [43], the range can span across the sensory detection threshold reported in water of approximately 2 g/L [44] and has been linked to wine "body" previously [45].…”
Section: Assessing the Association Of Pmt And 2fmt With Smoky/mentioning
confidence: 99%
“…Using odour addition studies, the ethyl esters conferring "peach" aroma in Chardonnay have only recently been demonstrated [20], while the source of "sweetness" in sugar dry white wines is not well understood. In dry red wines, the residual amino acid proline has been shown to increase "sweetness," "viscosity," and fruit favours [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hypothesis gaining more traction is that minerality comes from reductive wine-making and storage processes that produce or maintain sulphurous compounds, but not enough to spoil the wine with of favours [4,20,21]. For example, insufcient yeast assimilable nitrogen (YAN) in wine must can lead to the production of more permanent sulphur compounds (such as methionol) as opposed to the highly volatile forms (such as hydrogen sulphide, ethanethiol, and methanethiol) that have low boiling points and volatilise when a bottle of wine is aerated [20].…”
Section: Introductionmentioning
confidence: 99%
“…A major difculty is that agreement has not been reached on what minerality is in terms of its sensory profle [25] or, equally problematic, that the sensations referenced are too numerous. Minerality remains an ill-defned concept [5,21]. Nonetheless, most wine professionals and consumers maintain it is a real and distinct sensation, for example, Szymanski [13].…”
Section: Introductionmentioning
confidence: 99%